"Stepping Up" Activity Poststroke: Ankle-Positioned Accelerometer Can Accurately Record Steps During Slow Walking. Issue 3 (1st March 2016) - Klassen, Tara D.; Simpson, Lisa A.; Lim, Shannon B.; Louie, Dennis R.; Parappilly, Beena; Sakakibara, Brodie M.; Zbogar, Dominik; Eng, Janice J.
Abstract : Background: As physical activity in people poststroke is low, devices that monitor and provide feedback of walking activity provide motivation to engage in exercise and may assist rehabilitation professionals in auditing walking activity. However, most feedback devices are not accurate at slow walking speeds. Objective: This study assessed the accuracy of one accelerometer to measure walking steps of community-dwelling individuals poststroke. Design: This was a cross-sectional study. Methods: Two accelerometers were positioned on the nonparetic waist and ankle of participants (N=43), and walking steps from these devices were recorded at 7 speeds (0.3–0.9 m/s) and compared with video recordings (gold standard). Results: When positioned at the waist, the accelerometer had more than 10% error at all speeds, except 0.8 and 0.9 m/s, and numerous participants recorded zero steps at 0.3 to 0.5 m/s. The device had 10% or less error when positioned at the ankle for all speeds between 0.4 and 0.9 m/s. Limitations: Some participants were unable to complete the faster walking speeds due to their walking impairments and inability to maintain the requested walking speed. Conclusions: Although not recommended by the manufacturer, positioning the accelerometer at the ankle (compared with the waist) may fill a long-standing need for a readily available device that provides accurate feedback for the altered and slow walking patterns that occur with stroke.